ANALYSIS OF MACRO- AND MICRO ELEMENTS IN PLANTS FOALFOOT (TUSSILAGO FARFARA), CELERY (APIUM GRAVEOLENS), POTATO (SOLANUM TUBEROSUM) (Scientific journal of the Fergana State University, 2023)
In this article, the amount of macro- and microelements contained in the plants of foalfoot (Tussilago farfara), celery (Apium graveolens), potato (Solanum tuberosum) is determined by mass spectrophotometry with inductively coupled plasma, and the results of their comparison. The studied samples were rich in elements of calcium, magnesium, potassium, iron in their composition, it was proposed to create new dietary supplements that will help in the treatment of bone diseases, cardiovascular system, anemia.